Nuevos registros de hongos desertícolas en los Parques Nacionales Nevado Tres Cruces y Pan de Azúcar, Región de Atacama, Chile - Troncoso, Sandra; Casanova Katny, Angélica; Marín, Catalina; Palfner, Goetz (Gayana Botánica, 2020)
New records of fungi, forming two associations with contrasting fruiting body morphology and ecological preferences are reported from the Chilean desert, viz.: the agaricoid Conocybe cf. tenera and Coprinus comatus associated with riparian grassy environments in the high Andean Nevado Tres Cruces National Park and gasteroid Geastrum floriforme and Tulostoma spp. together with sequestrate Montagnea arenaria, all associated with xerophilic shrub vegetation on sand in the coastal fog zone of Pan de Azúcar National Park.